Stakeholder Pressures And Environmental Performance - Kassinis, George; Vafeas, Nikos (Academy of Management Journal, 2006)
We examine the connection between the internal heterogeneity of stakeholder groups and the resource dependence dynamics characterizing their relationships with firms. Empirically, we test how this heterogeneity is related to environmental performance and document a positive relationship between community stakeholder pressures and environmental performance at the plant level. Our results suggest that varying stakeholder characteristics and the dependencies associated with them are related to varying levels of environmental performance. Further, managers recognize that their organizations’ dependence on stakeholders is not uniform and take this dependence into account when shaping policies toward the natural environment.